Awareness on Child Marriage and its Consequences on Health among Chepang Community Madi, Chitwan - Paudel, Madhu Maya; Dura, Kalpana (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Child marriage is considered as social and health concern in Nepal, particularly in marginalized communities like Chepang. The study aim was to assess the level of awareness about child marriage and its health consequences among Chepang communities of Madi, Chitwan. Methods: A descriptive cross-sectional study was conducted among 98 participants of Chepang communities from 15 to 30 years age group. Data was collected through semi-structured interview schedule and analyzed using descriptive and inferential statistics such as frequency, percentage, mean, standard deviation and chi-square. Results: The finding of the study revealed that more than two third of the respondents (76,5%) had adequate level of awareness regarding child marriage and its consequences. However, significant portion of the respondents had inadequate awareness about legal provision of child marriage. There was no significant association between levels of awareness on child marriage with selected sociodemographic variables of the respondents. Conclusions: The study concludes that most of the respondents had adequate level of awareness about child marriage and its consequences. However, many of them still lacked a clear understanding on the legal aspects of child marriage.